2020
DOI: 10.1371/journal.pone.0234999
|View full text |Cite
|
Sign up to set email alerts
|

Sublethal concentrations of undissociated acetic acid may not always stimulate acid resistance in Salmonella enterica sub. enterica serovar Enteritidis Phage Type 4: Implications of challenge substrate associated factors

Abstract: Acid adaptation enhances survival of foodborne pathogens under lethal acid conditions that prevail in several food-related ecosystems. In the present study, the role of undissociated acetic acid in inducing acid resistance of Salmonella Enteritidis Phage Type 4 both in laboratory media and in an acid food matrix was investigated. Several combinations of acetic acid (0, 15, 25, 35 and 45 mM) and pH values (4.0, 4.5, 5.0, 5.5, 6.0) were screened for their ability to activate acid resistance mechanisms of pathoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 58 publications
(89 reference statements)
0
3
0
Order By: Relevance
“…Water sanitation and/or acidification is a promising practice for lowering the use of antibiotics in human and veterinary medicine [ 18 , 19 , 20 ]. However, the existence of knowledge gaps on the antibacterial activity of the commercially available water disinfectants, acidifiers, and glyceride blends, as well as the potential for microbes to develop resistance to these alternative biocides [ 27 , 28 , 29 , 30 ], emphasizes the significance of future research [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Water sanitation and/or acidification is a promising practice for lowering the use of antibiotics in human and veterinary medicine [ 18 , 19 , 20 ]. However, the existence of knowledge gaps on the antibacterial activity of the commercially available water disinfectants, acidifiers, and glyceride blends, as well as the potential for microbes to develop resistance to these alternative biocides [ 27 , 28 , 29 , 30 ], emphasizes the significance of future research [ 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are many knowledge gaps concerning the ability of bacteria to develop resistance to these alternative antimicrobials [ 27 , 28 , 29 , 30 ]. There is evidence that residual levels of applied acidic blends or disinfectants may trigger adaptation to oxidative stress by genetic mutations and/or horizontal transfer of antimicrobial resistance genes among the exposed bacteria [ 29 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Zhang et al (2020) reported that SCFAs in a broth medium with a pH of 6.5 were able to inhibit the growth of E. coli, whereas a neutral pH stimulated its growth. Foodborne pathogens, including C. sakazakii, can develop acid resistance when exposed to sub-lethal concentrations of acetate, although the adaptation is influenced by the acid concentration and the pH of the environment (Arnold et al, 2001;Álvarez-Ordóñez et al, 2012;Gavriil et al, 2020). E. coli can adapt to the acid stress induced by SCFAs at a neutral pH by regulating the expression of rpoS (Arnold et al, 2001).…”
Section: Discussionmentioning
confidence: 99%